Paracoccidioides spp.: the structural characterization of extracellular matrix, expression of glucan synthesis and associated genes and adhesins during biofilm formation - Oliveira, Lariane Teodoro [UNESP]; Marcos, Caroline Maria [UNESP]; Cabral, Ana Karla Lima Freire [UNESP]; Medina-Alarcón, Kaila Petronila [UNESP]; Pires, Regina Helena; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Frontiers, 2024)
The genus Paracoccidioides includes Paracoccidioides lutzii and the Paracoccidioides brasiliensis complex, which comprises four phylogenetic species. A key feature distinguishing planktonic growth from biofilm is the presence of a 3D extracellular matrix (ECM). Therefore, in this study, we analyzed biofilm formation in different species of Paracoccidioides yeast phase, characterized the structural elements of the matrix of P. brasiliensis (Pb18), P. lutzii (Pl01 and 8334) and P. restrepiensis (339 and 192) and evaluated the expression of glucan genes, according to the stage of biofilm evolution for P. brasiliensis. The strains were cultivated in planktonic and biofilm form for 24–144 h. The fungi biomass and metabolic activity were determined by crystal violet and tetrazolium salt reduction (XTT) tests and colony-forming unit (CFU) by plating. The biofilm structure was designed using scanning electron microscopy and confocal laser scanning microscopy techniques. The extracellular matrix of P. brasiliensis and P. lutzii biofilms was extracted by sonication, and polysaccharides, proteins, and extracellular DNA (eDNA) were quantified. The RNA was extracted with the Trizol® reagent and quantified; then, the cDNA was synthesized to analyze the enolase expression, 14-3-3, FKS1, AGS1, GEL3, and KRE6 genes by real-time PCR. All strains of Paracoccidioides studied form a biofilm with more significant metabolic activity and biomass values in 144 h. The extracellular matrix of P. brasiliensis and P. lutzii had a higher content of polysaccharides in their composition, followed by proteins and eDNA in smaller quantities. The P. brasiliensis biofilm kinetics of formation showed greater expression of genes related to glucan's synthesis and its delivery to the external environment in addition adhesins during the biofilm's adhesion, initiation, and maturation. The GEL3 and enolase genes increased in expression within 24 h and during the biofilm maturation period, there was an increase in 14-3-3, AGS1, and FKS1. Furthermore, at 144 h, there was a decrease in KRE6 expression and an increase in GEL3. This study highlights the potential for biofilm formation for three species of Paracoccidioides and the main components of the extracellular matrix that can contribute to a better understanding of biofilm organization.
Keywords: adhesins; biofilm; extracellular matrix; glucans; Paracoccidioidesspp; qRT-PCR